Frações de carbono e atributos biológicos em solos no semiárido de Pernambuco - BARROS, Raquel Bezerra de (2017)
The Caatinga is an exclusively Brazilian biome, however, studies that evaluate biological attributes in soils in the semi-arid Pernambuco are still very scarce. Also, due to the great seasonality of these regions, and in the state of Pernambuco, in which the forecasts focus mainly on the Agreste and Sertão environments, time monitoring studies are essential to evaluate the magnitude of temporal dynamics in soil attributes. The objective of this work was to evaluate the variation of biological attributes, carbon management indices and humic substances in Caatinga soils in the semi - arid region of Pernambuco in dry and rainy seasons. Soil samples were collected in microregions: Agreste and Sertão in the semiarid region of Pernambuco. In the Agreste environment, 8 areas were chosen, four of which were under native Caatinga (CN) and four were related to agricultural uses (AGR) and in the Sertão environment, 12 areas were chosen, six of them under CN and six of AGR uses. Sampling was carried out from five simple samples per layer (0-5, 5-10 and 10-20 cm), to form a composite sample with the aid of soil medium / clayey soils and with the aid of a shovel to Sandy soils. In each area three composite samples were collected. The collections were made semi-annually for two years, beginning in Sep / 2014 and ending in June 2016, being determined as collection 1 (COL.1), collection 2 (COL.2), collection 3 (COL.3) and collection 4 (COL.4). For the determination of the humic substances, the collections occurred annually 2014/2015. Soil samples were analyzed for biological attributes: CSA (water soluble carbon), total organic carbon (TOC), soil microbial biomass carbon (CBM), soil basal respiration (RBS), microbial quotient (qMIC), quotient (LC), non-labile carbon (CNL), lability (L), lability index (IL), carbon compartment index (CBI), carbon management index (BMI) and substances Humans (C-AF, C-AH and HUM). The results were evaluated by variance analysis and multivariate analysis, by main components (PCA) and clusters, to distinguish soils as a function of coverage and collection periods. The attributes that best explain the temporal variability of the soil uses in the Agreste are COT, qMIC, CL, ICC, IL and IMC, and for the COT, ICC, L and IMC Sertao. The PCA method distinguished soil cover in Agreste and Sertão. The biological attributes were not conclusive for the dry and rainy season. The conversion of CN in AGR use causes greater negative impacts in the Agreste in relation to the Sertão. The variables CSA, CBMS, qMIC and qCO2 in depth of 0-20 cm are the most sensitive to distinguish the soil cover in Agreste and Sertão de Pernambuco. The systems of agricultural uses used promoted significant impacts on the microbiological indicators evaluated. The variables CBM, RBS, qMIC and qCO2 are the most sensitive for soil cover differentiation and in different collection periods up to 20 cm depth. The condition of collection in dry or rainy periods was not determinant to differentiate microbial activity of the soil with the evaluated biological variables and soils of the semi-arid Pernambuco have low values of the fractions C-AF, C-AH and C-HUM.